A Service Management Mode Dealing with Information Leakage Risk in the Online Payment - Wu Xiao Gang; Zhou Wei Feng; Du Rong Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In view of personalinformation leakage risk in the process of online payment, this study putsforward a cloud protection system which can improve personal informationsecurity. The system includes two modules: personal information security modeland cloud service providers trust evaluation system. Among them, the personalinformation security model includes four layers design: the user, interface,platform and management layers. User layer is used to complete the userauthentication and login, interface layer is used for the classification andencryption of complex personal information, platform layer is used to completethe data storage, and the management layer is used to guarantee the overalleffectiveness of the system work. The cloud serviceproviders trust evaluation system based on the Theory of Membership Degree, canimprove the trust assessment level to cloud service providers. This study canensure the personal information security in the online sales, and be beneficialto the healthy development of e-commerce. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3704